Perceptions of Community Health Workers (CHW) on barriers and enablers to care for people with psychosis in rural Mozambique: findings of a focus group discussion study using the Capability, Opportunity, Motivation and Behaviour framework (COM-B framework) - Dirceu Mabunda; Déborah Oliveira; Mohsin Sidat; Francine Cournos; Milton Wainberg; Jair de Jesus Mari (BMC, 2022)
Abstract Background Psychotic disorders contribute significantly to the global disease burden by causing disability, impaired quality of life, and higher mortality in affected people compared with the general population. In rural settings, where there is limited or no access to healthcare, individuals living with psychotic disorders often seek support from Community Health Workers (CHWs). However, little is known about what CHWs know about psychosis and how they manage such cases. This study aimed to explore the CHWs perception of psychosis and their experiences and beliefs about the factors that might enable or hinder care-taking for patients with psychosis in rural settings in Mozambique. Methods A qualitative study was conducted in rural districts of Maputo Province, a southern region of Mozambique, using six focus group discussions with participation of 79 CHWs. Thematic analysis was used informed by the Capabilities, Opportunities, Motivation and Behaviour framework (COM-B). Results Nine primary themes were identified. Overall, CHWs perceived psychosis as treatable medical conditions and held a positive attitude about being part of the care-taking process of patients with psychosis in rural settings. Partnerships with key-stakeholders such as traditional healers, health care workers, and families, were perceived by CHWs as enablers to improve access to care in rural areas. However, stigma, myths, and lack of competencies to treat people with psychosis were perceived by CHWs as barriers for appropriate care. Conclusion CHWs, with adequate support, could play an important role in the care of patients with psychosis in rural settings, including identifying patients requiring care and referring them to appropriate healthcare professionals, and following up medicated patients with psychosis. Training of CHWs should consider inclusion of basic mental health care competencies.